Quantifying radiation from thermal imaging of residential landscape elements - Loveday, Jane; Loveday, G.; Byrne, Joshua; Ong, Boon; Newman, Peter (2017)
The microclimate of a residential landscape can affect both the energy use in your home and the human thermal comfort in your garden, ultimately affecting the heat in the neighbourhood or precinct. A thermal imaging camera provides information about the temperature of surfaces. By using Stefan–Boltzmann’s law and the surface properties, these temperatures can be used to calculate the emission of longwave radiation (radiant exitance) in W m-2. A thermal camera was used to determine the amount of radiant exitance from a range of residential landscape elements. A standard procedure for capturing these images was developed, taking into account factors which affect the quality of the radiometric data. A quantitative database comparing this radiation has been compiled for different times of day and different seasons. The sky view factor of these elements was chosen such that it was as close to 1 as possible. For a particular landscape design, areas of each landscape element can be measured and the amount of radiation reduced or emitted at different times can be calculated. This data can be used to improve landscape designs to reduce home energy use and human thermal comfort through shading and reduction of surfaces which emit longwave radiation close to the house.